Understanding the differentiating impacts of the communication strategies of a high involvement service (investment advisory services) and a high involvement product (precious jewellery) on customer satisfaction and loyalty. - Gupta, Gauri (2009)
While marketing literature has largely focused on high and low involvement purchases and the positive relationship between customer satisfaction and loyalty; the differentiating impacts of communication strategies for a high involvement service and a high involvement product on customer satisfaction and loyalty has received little academic attention. Consequently, this study examines the differentiating impacts of the communication strategies for investment advisory services and precious jewellery on customer satisfaction and loyalty respectively. The research was conducted using a mixed method approach, that is through 10 qualitative interviews, followed by a quantitative study conducted through a survey with 40 respondents which was analysed with the help of a conceptual framework using a regression and a correlation. The findings and results reveal that the communication strategies of a high involvement service as compared to a high involvement product have a greater impact on customer satisfaction and loyalty on account of the higher risk associated with the intangibility nature of a service. Moreover, it was found that satisfaction for a high involvement luxury product such as precious jewellery is more dependent on other factors such as physical attributes and quality. Lastly, the positive relationship between customer satisfaction and loyalty was found to be greater in the case of a high involvement service as compared to a high involvement product.